2010
DOI: 10.1016/j.ecss.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Fish under influence: A macroecological analysis of relations between fish species richness and environmental gradients among European tidal estuaries

Abstract: Estuarine fish assemblages are subject to a great environmental variability that largely depends on both upstream fluvial and downstream marine influences. From this ecohydrological view, our study introduces a macroecological approach aiming to identify the main environmental factors that structure fish assemblages among European tidal estuaries.The present paper focuses on the influence of large scale environmental gradients on estuarine fish species richness. The environment of 135 North-eastern Atlantic es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 60 publications
1
62
1
2
Order By: Relevance
“…We were unable to assess the relationship between plasticity of life history patterns and the area of the river basin and estuary, continental platform width or river discharge. These factors are among the main factors influencing the structure of estuarine fish assemblages (Nicolas et al 2010) and flounder juvenile recruitment (Martinho et al 2009). The inter-annual variability of river discharge may be an indirect driver of flounder life history plasticity, probably due to its control in setting estuarine productivity (Whitfield 1994, Loneragan & Bunn 1999 and in influencing the rate of direct and indirect recruitment of fishes in estuaries (Chícharo et al 2001).…”
Section: Ecological Significance Of Flounder's Diversified Life Histomentioning
confidence: 99%
“…We were unable to assess the relationship between plasticity of life history patterns and the area of the river basin and estuary, continental platform width or river discharge. These factors are among the main factors influencing the structure of estuarine fish assemblages (Nicolas et al 2010) and flounder juvenile recruitment (Martinho et al 2009). The inter-annual variability of river discharge may be an indirect driver of flounder life history plasticity, probably due to its control in setting estuarine productivity (Whitfield 1994, Loneragan & Bunn 1999 and in influencing the rate of direct and indirect recruitment of fishes in estuaries (Chícharo et al 2001).…”
Section: Ecological Significance Of Flounder's Diversified Life Histomentioning
confidence: 99%
“…Although this pattern of recovery is probably related to the changes in oxygen concentration in bottom layers, it also coincides with sufficient food availability to support permanent colonisation of these inner estuary locations. After the start of colonisation, however, the near complete recovery was achieved in 10 years, probably due to the wellknown contribution of marine species to the total species richness within the estuaries (Nicolas et al 2010). We emphasise that recovery from temporary ecosystem loss, such as water quality problems (including anoxia), may take less time than recovery from permanent ecosystem loss (such as land claim), where the appropriate lost ecosystem needs to be created (also see and references therein).…”
Section: From Hydrologicalmorphological Modificationmentioning
confidence: 99%
“…While later analyses of these data did include tests for differences in fish guild contributions between estuary types within each bioregion and vice versa (Harrison and Whitfield 2008), focus was again not placed on an explicit comparison of the importance of each spatial scale. Moreover, whereas Edgar et al (1999) and Nicolas et al (2010) both rigorously identified the combination of individual environmental variables at a system-wide and, to a lesser extent, regional scale1 that best reflected spatial differences in the fish faunas across many estuaries throughout Tasmania (71) and Europe (135), respectively, they also did not aim to quantify the relative importance of those scales or include local-scale factors. While Sanvicente-Añorve et al (2011) did test how spatial scales, as a whole, differ in their ability to explain differences in estuarine fish faunas along the Mexican Atlantic coast, they included only inter-estuary and, to a lesser extent, regional scales in their study.…”
Section: Introductionmentioning
confidence: 99%